Neoplastic and Non-neoplastic Bone Lesions of the Knee - Expósito, Diana; Martel, José; Alvarez de Sierra, Beatriz; Bueno, Angel; Vilanova, Cristina; Vilanova, Joan C. (Seminars in Musculoskeletal Radiology, 2024)
Numerous anatomical variants are described around the knee, many of which look like bony lesions, so it is important to know them to avoid unnecessary complementary tests and inadequate management. Likewise, several alterations in relation to normal development can also simulate bone lesions.However, numerous pathologic processes frequently affect the knee, including traumatic, inflammatory, infectious, and tumor pathology. Many of these entities show typical radiologic features that facilitate their diagnosis. In other cases, a correct differential diagnosis is necessary for proper clinical management.Despite the availability of increasingly advanced imaging techniques, plain radiography is still the technique of choice in the initial study of many of these pathologies. This article reviews the radiologic characteristics of tumor and nontumor lesions that may appear around the knee to make a correct diagnosis and avoid unnecessary complementary radiologic examinations and inadequate clinical management.
Keywords: knee; bone lesions; tumors; normal variant; developmental disorder